Acute pancreatitis during valproic acid administration in a patient with vascular dementia, epileptic seizures, and psychiatric symptoms: a case report - Mako Yanaga; Naomichi Okamoto; Reia Hashimoto; Ryohei Igata; Yuki Konishi; Atsuko Ikenouchi; Naoki Isomoto; Takahiro Shinkai; Masaru Harada; Reiji Yoshimura (Journal of Medical Case Reports, 2023)
Abstract Background Valproic acid (VPA) is a relatively safe drug widely used for the treatment of epileptic seizures and mania in bipolar disorder, as well as the prevention of migraine headaches. Here, we present a case of VPA-induced pancreatitis in a patient with vascular dementia, epileptic seizures, and psychiatric symptoms. He had no distinctive abdominal symptoms. Case presentation A 66-year-old Japanese man was treated with VPA for agitation and violent behavior due to vascular dementia, epileptic seizures, and psychiatric symptoms. During admission, he experienced a sudden decrease in consciousness and blood pressure. Abdominal findings were unremarkable; however, blood tests showed an inflammatory response and elevated amylase levels. Contrast-enhanced abdominal computed tomography showed diffuse pancreatic enlargement and inflammation extending to the subrenal pole. VPA-induced acute pancreatitis was diagnosed, VPA was discontinued, and high-dose infusions were administered. Acute pancreatitis resolved after treatment initiation. Conclusions Clinicians should be aware of this relatively rare side effect of VPA. Diagnosis may be challenging in elderly people and patients with dementia as they may present with non-specific symptoms. Clinicians should consider the risk of acute pancreatitis when using VPA in patients who cannot report spontaneous symptoms. Blood amylase and other parameters should be measured accordingly.